A time series approach to the monetary sector of the South African economy - Dietzsch, Carl Heinrich (University of Cape Town, 2016)
Bibliography: p. 111-114. === This thesis provides an investigation of the applicability of time series analysis to the process of economic model building. Chapter l explains the position of the Box-Jenkins approach to time series analysis in relation to other techniques of analysis. In Chapters 2 and 3 the theory of model building is discussed. In Chapter 4 an econometric model is analysed in detail from a time series approach.